First ionospheric experimental campaign and observations at Fraser's Hill, Malaysia: Results of vertical sounding - Mohd. Zain A.F.; Abdullah M.; Hwa H.Y.; Rhazali Z.A.; Abdullah S.; Gaik K.H. (2023)
The ionosphere over Malaysia is unique because of her location near the equator where the existence of the equatorial anomaly, electrojet, and fountain effect have made it good for studies. As part of a rejuvenation process in investigating the equatorial ionosphere in Malaysia, a short duration ionospheric experimental campaign was carried out at fraser's Hill (lat, 3 42,9' N, long. 101 44.2' E, at an altitude of 1298 m)fmm August 1 to 18, 2005. Two setls of equipment were installed; a digital ionosonde and a dualfrequency GPS receiver. This paper reports on the measurements obtained from the ionosonde. The system consists of the sounding equipment using a delta antenna for transmitting and a dipole antenna for receiving. The observable F-layer for this site can be seen in the late evenings around 18:00 UTC The observed critical frequency for this layer varies from 4 MHz to 6 MHz, The lower critical frequency can be seen between 21:00 and 00:00 UTC. Other observed phenomena were spread-F and sporadic-E. 2005 IEEE.